COVID-19 Pandemic and Violence Against Children - Aris Tristanto (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2022)
Abstract - During the COVID-19 pandemic, it is known that the number of violence against children in Indonesia is increasing. This study is a literature review with the aim of studying the reasons for violence against children during the COVID-19 pandemic and its prevention efforts. Common causes of violence in children during the COVID-19 pandemic are economic problems due to restrictions on activity during the pandemic, unbalanced relationships between children and parents, and low parental knowledge regarding parenting. The short-term impact of violence felt by children is the physical impact of the child, while the long-term impact is related to the child's soul. In overcoming the problem of violence against children during the COVID-19 pandemic, it must be done in a social environment with various prevention efforts. In this study, the authors suggest that there is a need for awareness, that acts of violence against children are extraordinary crimes that can interfere with children's growth and development. Keywords: children, violence, pandemic Abstrak - Selama masa pandemi COVID-19, diketahui bahwa angka kekerasan terhadap anak di Indonesia semakin meningkat. Studi ini adalah kajian pustaka dengan tujuan untuk mempelajari alasan terjadinya kekerasan terhadap anak selama pandemi COVID-19 dan upaya pencegahannya. Faktor penyebab umum kekerasan pada anak di masa pandemi COVID-19 merupakan masalah ekonomi akibat pembatasan aktivitas selama pandemi, hubungan anak dengan orang tua yang tidak seimbang, dan rendahnya pengetahuan orang tua terkait pola asuh. Dampak jangka pendek dari kekerasan yang dirasakan anak adalah berdampak pada fisik anak, sedangkan dampak jangka panjangnya berkaitan dengan jiwa anak. Dalam mengatasi masalah kekerasan terhadap anak di masa pandemi COVID-19 harus dilakukan di lingkungan sosial dengan berbagai upaya pencegahan. Pada penelitian ini penulis menyarankan perlu adanya kesadaran, bahwa tindak kekerasan terhadap anak merupakan kejahatan luar biasa yang dapat mengganggu tumbuh kembang anak. Kata kunci: anak, kekerasan, pandemi